Indicators of Success for Mine Site Restoration in Tropical Moist Forest Ecosystems - Jasper, DA; Veneklaas, EJ; Nichols, OG; Tongway, DJ (Mine Closure 2006: Proceedings of the First International Seminar on Mine Closure, 2006)
Ecosystems in the tropics can vary substantially, despite occurring in the same latitudinal zone. However, a common feature is their high biodiversity, with more than 50% of all plant and animal species being found in tropical forests, despite only occupying 7% of the land area (Whitmore, 1984). Tropical moist forests are generally defined by rainfall exceeding 1700 mm annually, an even distribution of solar radiation and constant high temperatures (Grainger, 1993, in Holl and Cairns, 2002). Rainfall is evenly distributed throughout the year in some tropical moist forests, such as at the Ok Tedi mine site in Papua New Guinea, while others may have a distinct dry season (Holl and Cairns, 2002). Information regarding restoration of tropical forest ecosystems is relatively sparse, especially relating to restoration after mining. It is noteworthy that a review by Hartshorn and Whitmore (1999) only included one paper relating to mining rehabilitation (Parrotta and Knowles, 1997). Most tropical forest restoration literature focuses on abandoned farmland (Holl and Cairns, 2002), and on the development of forestry and agroforestry systems, aiming at maximizing productivity of a limited number of economically-important species (Parrotta, 2002). It has been less common for restoration projects to aim at creating a diverse ecosystem of locally-occurring species that resembles that believed to formerly occupy the landscape. In this paper, we review indicators that may have application in assessing mine rehabilitation in tropical moist forests, in the context of experience at mines on Misima Island and at Ok Tedi.